Successful Retrieval of A Migrated Guide Wire Using an Angioplasty Balloon and Guiding Catheter - Cui, Linxian; Lu, Jing; Malhotra, Rajeev; Tian, Wenjie (Cardiology and Cardiovascular Medicine, 2020)
Loss of a guide wire in the radial artery is an occasional complication occurring with transradial catheterization. We report a novel, simple approach for retrieval of a migrated guide wire after failure to capture the guide wire with a gooseneck snare.